2016
DOI: 10.1158/2326-6066.cir-15-0238
|View full text |Cite
|
Sign up to set email alerts
|

Possible Interaction of Anti–PD-1 Therapy with the Effects of Radiosurgery on Brain Metastases

Abstract: Delayed radiation-induced vasculitic leukoencephalopathy related to stereotactic radiosurgery (SRS) of brain metastases has been reported to manifest clinically 9 to 18 months after treatment. Immune-modulating therapies have been introduced to treatment regimens for malignancies with metastatic predilection to the brain. The interaction of these systemic therapies with other modalities of treatment for brain metastases, namely, SRS, has not been fully characterized. We report two patients with metastatic mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Our search did not find studies on concurrent pembrolizumab and SRT. For nivolumab, only 1 case report of SRT for NSCLC brain metastases and 1 retrospective study of SRT for melanoma brain metastases was identified [41,42]. The case report by Alomari et al observed a grade 4 cerebral oedema in one patient receiving concurrent therapy [41].…”
Section: Toxicity Of Concurrent Srt and Immune Checkpoint Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search did not find studies on concurrent pembrolizumab and SRT. For nivolumab, only 1 case report of SRT for NSCLC brain metastases and 1 retrospective study of SRT for melanoma brain metastases was identified [41,42]. The case report by Alomari et al observed a grade 4 cerebral oedema in one patient receiving concurrent therapy [41].…”
Section: Toxicity Of Concurrent Srt and Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…For nivolumab, only 1 case report of SRT for NSCLC brain metastases and 1 retrospective study of SRT for melanoma brain metastases was identified [41,42]. The case report by Alomari et al observed a grade 4 cerebral oedema in one patient receiving concurrent therapy [41]. Ahmed et al reported two events of grade 3 cerebral oedema in 20 patients treated with SRT and nivolumab for melanoma brain metastases (Table 2) [42].…”
Section: Toxicity Of Concurrent Srt and Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…However, retrospective evidence has been contradictory, with select studies demonstrating a significant increase in intracranial inflammation and related toxicity after combined cranial RT and ICI therapy that was not observed in other studies. [16][17][18] Furthermore, the sequence and timing of cranial RT and ICI therapy is a theoretical modifier of the extent of potential immune synergy and therefore may have implications for both efficacy and toxicity. 19 However, the optimal timing of combined therapy has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Other ongoing studies are prospectively evaluating interactions between brain radiation therapy and immunotherapy because early results have suggested that combining these modalities may augment efficacy and perhaps toxicity. [71][72][73] PREGNANCY Metastatic cancer in pregnancy is a devastating condition leading to difficult decisions involving the mother and the developing fetus. PD1/PD-L1 interactions appear to play a key role in maintaining fetal tolerance; indeed, the placenta is often used as a positive control for PD-L1 expression because of its strong and ubiquitous expression.…”
Section: Brain Metastasesmentioning
confidence: 99%